Ten promotion and tenure tips for microbiologists and immunologists - Jacob S. Yount (mBio, 2024)
ABSTRACTIn this editorial, I share advice and general principles based on recent experiences as a mentor and evaluator for early-career microbiology and immunology faculty seeking promotion and tenure. I outline 10 recommendations covering research, service, teaching, and mentoring. In addition, I encourage nuanced conversations with colleagues to strategically navigate the unique promotion and tenure processes at different institutions. I hope that these practical tips will assist early-career faculty in attaining promotion and tenure, contributing to long-term scientific and career advances.